(untitled) (Revista Iberoamericana de Bioética, 2024)
Neglected Tropical Diseases (NTDs) are historically associated with poverty, resulting from social determinations that reproduce conditions of inequality and social and health vulnerability. Through a theoretical-reflective approach, based on Critical Bioethics frameworks, this article explores the social determinants and health determinations involved in the context of NTDs. The study points out that, from a dialectical historical-structural point of view, it is people in these situations who are primarily neglected and, consequently, the diseases. It is discussed that it is necessary to overcome the purely biomedical approach to NTDs and act on the social determinations that reproduce them. It is concluded that this should occur through the unveiling of the instrumental rationality that guides hegemonic approaches to NTDs, and through confrontation with the colonial hierarchies that keep people—and their diseases—neglected.